Output improvement of Sg. Piah run-off river hydro-electric station with a new computed river flow-based control system - Jidin R.; Othman B. (Institute of Physics Publishing, 2023)
The lower Sg. Piah hydro-electric station is a river run-off hydro scheme with generators capable of generating 55MW of electricity. It is located 30km away from Sg. Siput, a small town in the state of Perak, Malaysia. The station has two turbines (Pelton) to harness energy from water that flow through a 7km tunnel from a small intake dam. The trait of a run-off river hydro station is small-reservoir that cannot store water for a long duration; therefore potential energy carried by the spillage will be wasted if the dam level is not appropriately regulated. To improve the station annual energy output, a new controller based on the computed river flow has been installed. The controller regulates the dam level with an algorithm based on the river flow derived indirectly from the intake-dam water level and other plant parameters. The controller has been able to maintain the dam at optimum water level and regulate the turbines to maximize the total generation output. Published under licence by IOP Publishing Ltd.